2015
DOI: 10.1002/pd.4607
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ultrasound predictors of postnatal major cerebral abnormalities in fetuses with apparently isolated mild ventriculomegaly

Abstract: Prenatal ultrasound follow-up identifies fetuses at higher risk for a major cerebral abnormality among cases with isolated mild ventriculomegaly. In cases with persistent or progressive enlargement, fetal MRI and postnatal imaging seem appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 28 publications
0
31
3
Order By: Relevance
“…Our high rate of postnatally diagnosed additional brain anomalies differed from other data with a range of 7-17% [1,2,26]. In our study, most of the postnatally diagnosed brain anomalies were detected on postnatal MRI, which is in line with higher detection rates in postnatal MRI compared to postnatal ultrasound in other articles [21,25].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Our high rate of postnatally diagnosed additional brain anomalies differed from other data with a range of 7-17% [1,2,26]. In our study, most of the postnatally diagnosed brain anomalies were detected on postnatal MRI, which is in line with higher detection rates in postnatal MRI compared to postnatal ultrasound in other articles [21,25].…”
Section: Discussioncontrasting
confidence: 52%
“…The spectrum of postnatally diagnosed additional brain anomalies was different from that of a meta-analysis, where corpus callosal abnormalities and defects of the septum pellucidum were not reported [25] (n = 34), but similar to population-based data [2] and studies that incorporated fetal MRI [3,13,26] (Table 2).…”
Section: Discussionmentioning
confidence: 88%
“…Twenty-two fetuses (64.7%) with "Severe Ventriculomegaly" had associated anomalies; this rate is similar to the 65% reported by Breeze et al's (9), but higher than the 58% reported by Gaglioti et al (17). Previous study has also suggested that the rate of associated anomalies increased from 41% to 76% when the atrial width increased from 10-12.0 mm to 12-14.9 mm (17); however, we found no differences among the three groups in our study, and a recent study supports our findings (10). The different general populations of the studies might explain most of the differences, and improvements in prenatal imaging technology could increase the rates of associated abnormalities.…”
Section: Discussioncontrasting
confidence: 45%
“…This finding was similar to the findings of Kennelly et al (8), who reported that the first VM diagnosis occurred at 26.9 weeks gestational age (19-40 weeks); Breeze's study (9) also reported that severe VM was first diagnosed at 28 weeks gestational age (16-36 weeks). However, Baffero et al (10) reported an earlier gestational age at first diagnosis: 25.1 weeks. The differences might arise from the studies' different compositions; no severe ventriculomegaly cases were included in the Baffero et al study, and 34 severe VM cases (14.1%) were included in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation